Role of acid mixtures etching on the surface chemistry and sodium ion storage in Ti3C2Tx MXene. Issue 45 (30th April 2020) - Anayee, Mark; Kurra, Narendra; Alhabeb, Mohamed; Seredych, Mykola; Hedhili, Mohamed Nejib; Emwas, Abdul-Hamid; Alshareef, Husam N.; Anasori, Babak; Gogotsi, Yury
Abstract : Optimizing the etchants for MXene synthesis to remove etching byproducts, obtain pristine surface chemistry, and improve energy storage performance. Abstract : Two-dimensional transition metal carbides and/or nitrides (MXenes) have shown promise in developing electrochemical storage of metal ions within conductive galleries due to redox reactions with transition metal atoms. Here, effect of surface chemistry on electrochemical storage of sodium ions within MXene interlayers is investigated by etching Ti3 AlC2 MAX using different etchants – HF, HF/HCl, and HF/H2 SO4 .